Evolusi Metode Penetapan Hukum Islam: Analisis Kontribusi Sahabat Nabi Muhammad Saw - Muhammad Imam Maghudi; Lomba Sultan; Fatmawati F (Madani: Jurnal Ilmiah Multidisiplin, 2023)
This article starts the time of the Companions when he replaced the position of the Prophet Muhammad as leader of the people and head of state, not in a prophetic position. Among them, they were later elected as leaders with the title of caliph. During this time, there were major changes in people's lives, because the area of Islam had expanded and the lives of the people had become increasingly complex. This period was a very interesting period, because the development of Islamic law became dynamic. The reason for the dynamism is nash it no longer goes down, while problems in human life always arise and require legal answers. To find this answer, a legal determination method is needed.